A Hydroxylated Tetracationic Viologen based on Dimethylaminoethanol as a Negolyte for Aqueous Flow Batteries. Issue 1 (26th October 2022) - Caianiello, Carlo; Arenas, Luis F.; Turek, Thomas; Wilhelm, René
Abstract: A tetracationic viologen based on dimethylaminoethanol is reported as a novel negolyte for aqueous‐organic flow batteries. The compound (1, 1′‐bis(3‐((2‐hydroxyethyl)dimethylammonio)propyl)‐[4, 4′‐bipyridine]‐1, 1′‐diium tetrachloride), termed [(DMAE‐Pr)2 ‐Vi]Cl4, was prepared by replacing the trimethylammonium groups of a former analogue for dimethylaminoethanol derivatives as permanently charged moieties, improving its solubility and modifying its electronic structure, as revealed by DFT calculations. Its electrochemical properties and diffusion coefficient were investigated by voltammetry and DOSY. The battery concept was demonstrated by pairing [(DMAE‐Pr)2 ‐Vi]Cl4 with a TEMPOL posolyte using a low‐cost anion exchange membrane and a neutral‐pH supporting electrolyte. [(DMAE‐Pr)2 ‐Vi]Cl4 has great potential for enhancing energy density in viologen flow batteries. Abstract : Negolytes : A new hydroxylated tetracationic viologen was effectively prepared by selecting a dimethylaminoethanol derivative as permanently charged moiety. Intended for aqueous flow battery negolytes, the compound showed enhanced solubility and was characterized by NMR, DFT calculations, DOSY and electrochemical techniques. As proof of concept, it was paired with TEMPOL in a battery, enduring 300 galvanostatic cycles at 40 mA cm −2 using a low‐cost membrane.